Mycoplasma Genitalium And Streptococcus Agalactiae Colonization In Pregnant Women: An Emerging Relationship. (28th October 2020) - Hummel, K; Dunn, J; Muldrew, K; Gogia, S; Kravitz, E; Johnson, E; Berra, A; Stafford, I; Martin, I; Munson, E
Abstract: Introduction/Objective: Mycoplasma genitalium has been identified as an emerging sexually transmitted infection (STI) causing cervicitis, pelvic inflammatory disease and other gynecologic pathology. The prevalence of M. genitalium in pregnant women has not been determined, nor has frequency of co-infection with Streptococcus agalactiae (GBS). Neonatal sepsis caused by GBS is associated with black race and young maternal age with approximately 10%-30% of pregnant women colonized. The aim of this retrospective study was to investigate the possible association between M. genitalium infection and colonization with GBS in a large cohort of pregnant women from a tertiary care center in Houston, Texas. Methods: Remnant endocervical samples collected from pregnant women attending clinics at the Baylor College of Medicine between September 2019 and December 2019 were screened for M. genitalium by transcription mediated amplification (Hologic, Inc. Marlborough, MA). Demographic, STI co-infection [Human papillomavirus (types 16, 18), Trichomonas vaginalis, Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum, and Herpes simplex virus], and GBS status data were recorded. Fisher's exact test was performed for statistical analysis. Results: 719 total samples were collected and tested for M. genitalium. Of these, 41 (5.7%) were positive. The mean age of infected women was younger than noninfected women (24.9 vs. 28.1 years respectively p = 0.0004). More black women (34.2%) were infected with M. genitalium compared to white (14.6%) or other (51.2%) (p = 0.0003). Rates of GBS colonization was significantly higher among women infected with M. genitalium compared to women who tested negative (58.3% vs. 16.1% respectively p = 0.002) and increased compared to national reported rates of GBS colonization. M. genitalium also showed a significant association with T. vaginalis (p=0.03), but no other STI co- infections studied. Conclusion: Our data demonstrates that infection with M. genitalium may be associated with persistent GBS colonization. Further prospective studies are needed to further elucidate this relationship.